A SUBJETIVIDADE DO TEA NA ATIVIDADE AQUÁTICA (Fiep Bulletin - online, 2019)
The TEA is still a puzzle that needs the interaction and integration of all. Integration between the school, the studentand the family and between people who participate in the day to day of the TEA. Understanding that socialization and socialinclusion should always be privileged, despite the absence of important aspects in speech and language and behavioral aspects,which lead to a significant delay in their development.What is important to emphasize is that the teaching and learning of the TEA are not tied to an educational curriculum.Autistic subjectivity must be taken into account. Therefore, above all, one must seek to execute the activity without worrying aboutrules, since the most important is the formation of this individual and makes him independent and able to interact in society and tocarry out the activities proposed to them, even which subjectively.Throughout the course of swimming learning, the subjects behaved in the water and performed the educational onesfor swimming according to their understanding and absorption: this is subjective! Therefore, interventions at a sporting,recreational, therapeutic or educational level should and can serve as a support to the TEA humanization process, since it isunderstood that what is appropriate is to stimulate the fundamental aspects that are compromised and to lead them to a "better"Harnessing the human movement in their activities of daily life.
Keywords: Autism (TEA); Swimming; Subjectivity.